Sobreviver mulher: sujeitas às violências de gênero, sujeitas insurgentes do feminismo - Maíra Cristina Corrêa Fernandes (2018)
The subject of law is an abstract category erected in the paradigm of modernity, which brings universal values as equality, freedom and rationality. Throughout history, however, such meanings served as reference points for male experience, hiding the patriarchal logic present in the various gender violence against women. As a revolutionary subject of feminism, a fundamentally political movement in its origin, the discourse of the pretended universality of the juridical subject was strained for not reaching them, in the face of the maintenance of patriarchal domination. At the same time, however, feminism itself is also in the dilemma of seeking, through legal institutions, the recognition of women as subjects.